KALOBORASI DAN KOORDINASI PENYUSUNAN RBA UNIVERSITAS NUSA CENDANA TAHUN 2018 - Erastus Dominggus Benu; M.N.C.B Neolaka; Ajis S Adang Djaha (The Indonesian Journal of Public Administration (IJPA), 2020)
Abstract, Collaboration and coordination of the planning section with budget user units in terms of RBA preparation have not been established effectively and efficiently. Therefore, in this study researchers are interested in examining the collaboration and coordination built in preparing the University Budget Business Plan which is certainly an accumulation of programs and activities from all units in Undana as well as aspects that support and hinder the preparation of the RBA, so that the roots the problems in the drafting process have become more targeted and easily attainable. This study aims to identify the collaboration and coordination of the preparation of the Business Plan Budget (RBA) and to analyze aspects that support and hinder the preparation of the Business Plan Budget (RBA) of the University of Nusa Cendana in 2018. Research using qualitative descriptive methods. With data collection techniques of observation, interviews and documentation. collaboration and coordination that are built in preparing the University Budget Business Plan and aspects that support and hinder the preparation of the RBA, so that the root problems in the drafting process are more targeted and easily measured for achievement. The results of this study the preparation of the Budget Business Plan (RBA) is one of the important documents at the Public Service Board (BLU) satker. The formulation of the RBA began after the Determination of Undana as a BLU satker and the preparation of the RBA required intensive collaboration and coordination between units with the University so that there was synchronization of programs and activities in the preparation of the University RBA according to the prevailing mechanism. Collaboration and coordination have not been carried out effectively and efficiently. Key words: Collaboration, Coordination And Budget Abstrak, Kolaborasi dan koordinasi bagian perencanaan dengan unit-unit pengguna anggaran dalam hal penyusunan RBA belum terjalin secara efektif dan efisien. Oleh karena itu, dalam penelitian ini peneliti tertarik untuk meneliti kolaborasi dan koordinasi yang dibangun dalam menyusun Rencana Bisnis Anggaran Universitas yang tentunya merupakan akumulasi program dan kegiatan dari semua unit yang ada di Undana serta aspek-aspek yang mendukung dan menghambat penyususun RBA tersebut, agar akar permasalahan dalam proses penyusunan menjadi lebih terarah dan mudah di ukur ketercapaiannya. Penelitian ini bertujuan untuk mengengtahui kolaborasi dan koordinasi penyusunan Rencana Bisnis Anggaran (RBA) dan Untuk menganalisis Aspek-aspek yang mendukung dan menghambat penyusunan Rencana Bisnis Anggaran (RBA) Universitas Nusa Cendana tahun 2018. Penelitian menggunakan metode deskriptif kualitatif. Dengan teknik pengumpulan data  observasi, wawancara dan dokumentasi. kolaborasi dan koordinasi yang dibangun dalam menyusun Rencana Bisnis Anggaran Universitas dan aspek-aspek yang mendukung dan menghambat penyususun RBA tersebut, agar akar permasalahan dalam proses penyusunan menjadi lebih terarah dan mudah di ukur ketercapaiannya. Hasil penelitian ini Penyusunan Rencana Bisnis Anggaran (RBA) merupakan salah satu dokumen penting pada satker Badan Layanan Umum (BLU). Penyusunan RBA ini mulai dilakukan  setelah Penetapan Undana sebagai satker BLU dan Penyusunan RBA dibutuhkan kolaborasi dan koordinasi intensif antar unit dengan Universitas sehingga adanya sinkronisasi program dan kegiatan dalam penyusunan RBA Universitas sesuai mekanisme yang berlaku. Kolaborasi dan koordinasi belum dilakukan secara efektif dan efisien. Kata kunci: Kolaborasi, Koordinasi Dan Anggaran